Transactional distance and learner outcomes in an online EFL context. (2nd January 2021) - Kara, Mehmet
ABSTRACT: This mixed-method study aims to investigate learners' perceptions of transactional distance and the association of those perceptions with learner outcomes in an online English as a Foreign Language (EFL) context. Transactional distance theory formed the theoretical basis of the study. The quantitative data were collected from the learners enrolled in the five sections of an online EFL course offered within five online undergraduate programmes. Qualitative data were collected from the interview with the teacher of these five sections, learner responses in open ended questions, and observations on online course sections. The findings indicated that learners' perceptions in terms of transactional distance and learner outcomes were more than moderate. These perceptions did not significantly change in terms of learner demographics except in the case of perceived satisfaction. Females felt more satisfied with the course than males. The findings also revealed that the components of transactional distance significantly predict learner outcomes of perceived learning and satisfaction. Transactional distance between learner and interface made the greatest contribution to the prediction of perceived learning while transactional distance between learner and teacher made the greatest contribution to the prediction of perceived satisfaction. The qualitative findings elucidated the contextual factors influencing the quantitative findings.